Analyzing Factors Influencing Behavior Intention to Use Snapchat and Instagram Stories - Vincent Valiant Coa; Johan Setiawan (Universitas Multimedia Nusantara, 2017)
Snapchat, and Instagram are two social networks which recently gain their users after adopting such a feature called